Beyond vernacular Malay architecture : the perception on the conservation and adaptive reuse of old townhouses at Jalan Doraisamy, Kuala Lumpur - Denan, Zuraini (IIUM Press, 2011)

(untitled)
The research focuses on one ofthe latest conservation work done in Kuala Lumpur city, Dang Wangi area called Heritage Ro\v, beyond the Malay Vernacular Architecture in urban settings. The conservation of the historical buildings had revived the area to become one of the most frequently visited spot by the locals and tourists. The transformation from a tow"nhouse built during 1920's to a leisure and entertainment business area is considered refreshing, compared to the old condition which was almost an abandoned part of the city. Most of people agreed that the conservation works were worthwhile and an excellent effort in enhancing the architecture, business and tourism of the city. The renovation works done on the external parts are still considered minimum in conserving the old structure and building image. The interior parts of these buildings were drastically changed to cater for the new functions. The evidences indicated that the area had become more of a collection of international fine dining restaurants and pubs as well as one of the favourite food and beverage area for tourist and locals.